Un método para medir el volumen radical de plantas de cacao (Theobroma cacao L.) cultivadas en hidroponia - Jiménez Sáenz, E.; Salazar, J.J; Picado, V. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A description is made of a simple apparatus which can be used either to determine root volume or water absorption, by a waterdisplacement device. It is easy to operate and repeated observations can be made in relatively short periods of time. This volumetric outfit consists of a cylindrical receptacle connected to a buret which has a sidearm adapted in such a way that suction can be applied through it. The materials used in its construction are pieces of broken glassware and other common laboratory accessories. The precision of the measurements, made with this apparatus, is very high and compares favorably with that of other outfits described in the literature.